Gold(I)-catalysed one-pot synthesis of chromans using allylic alcohols and phenols - Eloi Coutant; Paul C. Young; Graeme Barker; Ai-Lan Lee (Beilstein Journal of Organic Chemistry, 2013)
A gold(I)-catalysed reaction of allylic alcohols and phenols produces chromans regioselectively via a one-pot Friedel–Crafts allylation/intramolecular hydroalkoxylation sequence. The reaction is mild, practical and tolerant of a wide variety of substituents on the phenol.